Model Prencanaan Kurikulum Pada Rumah Peradaban Pelajar Indonesia (RPPI) dengan Importance and Performance Analysis (IPA) - Endin Mujahidin; Nesia Andriana; Rafika Waty, Hilda (Center of Language and Cultural Studies, 2023)
This study aims to analyze the application of the curriculum planning model implemented of Rumah Peradaban Pelajar Indoensia (RPPI). This study using the Importance and Performance Analysis (IPA) model and used primary data sourced from questionnaires which were distributed to thirty (30) respondents using the Service Quality (Servqual) method by a Likert scale of five. The results of this study shows that the RPPI institution uses the PPBS planning model (Planning, Programming, Budgeting System). The planning stages carried out by this institution are in the form of determining the vision and mission, objectives, program determination and selection of alternative programs based on managed funding. The results of the Importance Performance Analysis (IPA) shows that RPPI institution needs to strive to improve performance through the preparation and planning of service and managerial study rooms, learning facilities and scholarship services. The Institution needs to maintain the ability and insight of teachers who are very good, the superiority of the program guarantees provided and moral of development carried out. Management of service hours and its relation and communication has reached a fairly good level of satisfaction. In addition,the items for information provided to customers, and handling complaints has a low level of expectations with high service quality. Institutions must be able to maintain the stability of the level of satisfaction with the quality of performance, carry out activities according to the planned program and involve the participation of the community or other partnerships in monitoring program implementation and evaluation.